The emerging value of molecular forms of B-type natriuretic peptide in heart failure - Yang, Ning-I; Wang, Chao-Hung (Journal of Laboratory and Precision Medicine, 2017)
Brain natriuretic peptide (BNP) has an established role in diagnosing heart failure (HF) and has shown to provide independent prognostic information. However, its prognostic value has limitations, leading to the development of other prognostic biomarkers such as ST2 and galectin-3 (1,2). With recent advances, we have gained more understanding into the bioactivity and metabolism of BNP. In different individuals, there are actually many BNP fragments in the circulation as a response to the degradation process.